Virus Ebola-Reston. ¿el cerdo, un nuevo hospedador? - Sánchez-vizcaíno, Jose Manuel; Martínez-lópez, Beatriz; Mur Gil, Lina (Revista Complutense de Ciencias Veterinarias, 2009)
Ebola-Reston is species of the Ebola virus that was identified for the first time in 1989 in the United States. Several outbreaks have happened since then, affecting monkeys and humans in contact with these, without producing any disease or death in the latter. At the end of 2008 this virus was detected for the first time in pigs of two farms in the Philippines. The main objective of this work has been to analyze the unique outbreak of Ebola-Reston in pigs, and to perform an epidemiological analysis that could help to raise hypothesis about the origin of the virus.. The study of this outbreak confirms the pig as a new host, able to transmit the infection to other swine. This represents a new risk for animal health and public health, due to the virulence of the virus and the importance of the pig for human feeding.
Keywords: Ebola-Reston; Swine; Philippines; Epidemiology